التّحقّق من الخصائص السّيكومتريّة لمقياس جودة الحياة الوظيفيّة لدى أساتذة التّعليم الابتدائي. -دراسة ميدانية ببعض ابتدائيات بلديّة العش ولاية برج بوعريريج- - هرم غنية; مقدم كريمة; اشراف: بورنان سامية (جامعة محمد بوضياف -المسيلة, 2025)
تهدف الدراسة الحالية إلى التّحقّقمن الخصائص السّيكومترية لمقياس جودة الحياة الوظيفية لدى أساتذة التعليم الابتدائي ببعض ابتدائيّات بلدية العش بولاية برج بوعريريج، حيث تم التركيز في هذه الدراسة على الجانب الإحصائي المتمثل في الخصائص السّيكومترية (التّحقق من الصدق والثبات لمقياس جودة الحياة الوظيفيّة) لدى فئة أساتذة التعليم الابتدائي ببعض ابتدائيات بلدية العش الواقعة بولاية برج بوعريريج، ومن أجل ضمان الحصول على مؤشرات مناسبة للخصائص السّيكو مترية وأيضا تحقيق أهداف هذه الدراسة طبقت الباحثتان المقياس على عينة قدرها 130 أستاذا وأستاذة، المستمدة من مجتمع الدراسة المقدّر بـ190أستاذ، وفي النهاية توصلت الدراسة الى النتائج التالية: المقياس بتمتع بدرجة عالية من الصدق من خلال عرضه على محكمين و الوصول إلى اتفاق بينهم وبالتالي أصبح المقياس يتمتع بصدق محتوى مناسب، كما تمّ التّحقق من الصّدق أيضا من خلال دراسة الاتساق بين الأبعاد والدرجة الكليّة للمقياس، أيضا المقياس يتمتع بالثبات من خلال التطبيق وإعادة التطبيق وطريقة ألفا كرونباخ، حيث وجد أن هناك ثبات واستقرار في النتائج، تمّ أيضا اختبار النّموذج العاملي التوكيدي لمفهوم جودة الحياة الوظيفية ببرنامج AMOS، فكانت النتائج تشير إلى مؤشّرات مطابقة ضعيفة بين النّموذج والبيانات وبالتالي تمّ رفض الفرضية الخاصة بذلك. كلمات مفتاحية: جودة الحياة الوظيفية، الصّدق، الثّبات. مؤشّرات المطابقة.   Abctract: Study Title: Verifying the psychometric properties of the quality of work life scale among primary education teachers-A field study in some elementary schools in the municipality of Al-Ash-BordjBouArreridj Province. The current study aims to investigate the psychometric properties of a measure of the quality of work life among professors Primary education in some elementary schools in the municipality of El-Ash, in the state of BordjBouArreridj . The focus of this study was on the statistical aspect represented by psychometric properties. Verifying the validity and reliability of the Quality of Work Life Scale. In the category of primary education teachers in some elementary schools in the municipality of El-Ash, located in the state of BordjBouArreridj. In order to ensure obtaining appropriate indicators of psychometric characteristics and also to achieve the objectives of this study. The two researchers applied the scale to a sample of 130 male and female professors . Derived from the study population estimated at 190 professors. In the end, the study reached the following resultsthe scale enjoys a high degree of validity by presenting it to the arbitrators and reaching agreement among them. Thus, the scale has adequate content validity . Validity was also verified by studying the consistency between the dimensions and the total score of the scale. The scale also enjoys reliability through application and reapplication and the Crombach alpha method . It was found that there is consistency and stability in the results. The confirmatory factor model of the concept of quality of work life was tested and tested with a programAMOS. The results indicated poor matching indicators between the model and the data, and therefore the hypothesis was rejected. key words:Quality of work life , honesty and persistence, Conformity indicators.